Partisipasi Masyarakat dalam Meningkatkan Ekowisata Mangrove di Desa Denai Kuala, Kabupaten Deli Serdang - Meilinda Suriani Harefa; Restu Restu; Theresia Margaretha Gulo; Irfan Ruhaimi; Jenni Novita Sianturi (Pusat Riset dan Inovasi Nasional, 2024)
Mangrove ecotourism offers a variety of interesting tourist activities for visitors, such as nature tourism, environmental education, and cultural tourism. The purpose of this study was to determine the role and efforts of the community in participating in improving mangrove ecotourism management in Denai Kuala Village, Pantai Labu District, Deli Serdang Regency. The method used in this research is Qualitative with Descriptive Approach. The results of this study show that there are various types of mangroves in Denai Kuala village such as Rhizopora Apicullata, Rhizophora Mucronata and Avicennia. Beach management with an approach that harmonizes environmental protection, animal welfare, education, and economic sustainability. Mangrove ecotourism management on Putra Deli beach is managed by one party where the management of the beach revenue is used properly and partly goes into the treasury as a further beach management fund. Mangrove management of Muara Indah Beach is carried out by groups of people who live around the beach. Not all people are only some who belong to the Muara Indah Beach management group